Potential role of vector-mediated natural selection in dengue virus genotype/lineage replacements in two epidemiologically contrasted settings. Issue 1 (1st January 2021) - O'Connor, Olivia; Ou, Tey Putita; Aubry, Fabien; Dabo, Stéphanie; Russet, Sylvie; Girault, Dominique; In, Saraden; Minier, Marine; Lequime, Sebastian; Hoem, Thavry; Boyer, Sébastien; Dussart, Philippe; et al.
ABSTRACT: Dengue virus (DENV) evolutionary dynamics are characterized by frequent DENV genotype/lineage replacements, potentially associated with changes in disease severity and human immunity. New Caledonia (NC) and Cambodia, two contrasted epidemiological settings, respectively experienced a DENV-1 genotype IV to I replacement in 2012 and a DENV-1 genotype I lineage 3–4 replacement in 2005–2007, both followed by a massive dengue outbreak. However, their underlying evolutionary drivers have not been elucidated. Here, we tested the hypothesis that these genotype/lineage switches reflected a higher transmission fitness of the replacing DENV genotype/lineage in the mosquito vector using in vivo competition experiments. For this purpose, field-derived Aedes aegypti from NC and Cambodia were orally challenged with epidemiologically relevant pairs of four DENV-1 genotype I and IV strains from NC or four DENV-1 genotype I lineage 3 and 4 strains from Cambodia, respectively. The relative transmission fitness of each DENV-1 genotype/lineage was measured by quantitative RT–PCR for infection, dissemination, and transmission rates. Results showed a clear transmission fitness advantage of the replacing DENV-1 genotype I from NC within the vector. A similar but more subtle pattern was observed for the DENV-1 lineage 4 replacement in Cambodia. Our results support the hypothesis that vector-driven selection contributed to the DENV-1 genotype/lineage replacements in these two contrasted epidemiological settings, and reinforce the idea that natural selection taking place within the mosquito vector plays an important role in DENV short-term evolutionary dynamics.